ICT USAGE CHARACTERISTICS AND COMPUTER SECURITY - Akman, Ibrahim; Bostan, Atila (PEOPLE: International Journal of Social Sciences, 2018)
Although acquired-user security habits and user security awareness are qualified as the feeblest components in assuring the information and communication technologies security, they are deemed to be inevitable as well. While the technology in information processing domain efforts its best in establishing the highest plausible security, user awareness is still referred as the key-component. Human demographic factors, ICT usage frequency might have correlation with security related behavior routines, this dimension not to be known yet. Hence, in this study we examined the influence of ICT usage characteristics on secure computer usage behaviors. In order to investigate this relation, a survey was carried out with the participation of 466 individuals from diverse layers of the community. The results demonstrated that statistically noteworthy relations exist between several socio-demographic features, frequency and reason of ICT usage factors and secure computer usage.